2007
DOI: 10.1681/asn.2006101153
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil versus Azathioprine for Prevention of Chronic Allograft Dysfunction in Renal Transplantation

Abstract: The Mycophenolate Steroids Sparing (MYSS) study found that in renal transplant recipients who were on immunosuppressive therapy with the cyclosporine microemulsion Neoral, mycophenolate mofetil (MMF) was not better than azathioprine in preventing acute rejection at 21 mo after transplantation and was 15 times more expensive ; P ‫؍‬ 0.53), and adverse events were similar on azathioprine (n ‫؍‬ 124) and MMF (n ‫؍‬ 124), respectively. Outcomes in the two groups were comparable also among patients with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 39 publications
11
56
0
1
Order By: Relevance
“…But, given current evidence, azathioprine and mycophenolate mofetil appear to be similar in terms of acute rejection rates and long-term allograft survival rates. 35 Our results could be another evidence for this concept.…”
Section: Discussionsupporting
confidence: 57%
“…But, given current evidence, azathioprine and mycophenolate mofetil appear to be similar in terms of acute rejection rates and long-term allograft survival rates. 35 Our results could be another evidence for this concept.…”
Section: Discussionsupporting
confidence: 57%
“…20 At completion of the first 6-mo treatment period, steroid dosage was progressively tapered and eventually discontinued and patients were then followed for up to month 72 posttransplantation, with clinical and laboratory evaluations every 6 mo. 20,33 Genetic data and any other relevant information were retrieved from the study population without interfering with patient management and were handled according to standard regulations for data registration, use, and preservation of patient anonymity and privacy. The study protocol was approved by the Ethical Committee of the Coordinating Center and of all of the Transplant Centers involved in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Nine trials (eight maintenance studies 88,89,92,[110][111][112]122,148 and one study 148 of both induction and maintenance) reported significant baseline between-group differences for key factors, including PRA grade, number of previous transplants, patient age, pretransplant diabetes mellitus, HLA mismatches and ECD donor kidneys. A further six maintenance studies 91,101,130,133,140,155 were rated as 'partial' because they reported a baseline difference in patient sex.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The remaining trials (one induction study 97 and 20 maintenance studies 75,81,85,91,[99][100][101][102]104,109,110,112,114,115,117,[119][120][121][122]127 ) did not report any information about blinding participants to treatment allocation.…”
Section: Treatment Allocation Masked From Participantsmentioning
confidence: 99%
See 1 more Smart Citation